Program Penguasaan Ilmu Tajwid Dengan Mudah - Siregar, Anggreini; Husna, Nihayah; Huda, Nurul; Samira, Tursina (Maslahah: Jurnal Pengabdian Masyarakat, 2020)
The Qur’an is a holy book of Muslims who are guidelines in living life. By reading the Qur’an, it can be a helper in the hereafter. So that in reading the Qur’an is not arbitrary, there is knowledge that can be learned in understanding how to read the good and true Qur'an. This science is the science of Tajwid. The science of Tajwid is a branch of science to study the ways of reading the Qur’an. The law of reading the Qur'an with Tajwid is a Fardu a'in for every Muslim. For people who are especially not fluent in Arabic, it will be difficult in understanding the science tajwid. Then, here are some ways in mastering science tajwid easily, so it can be applied in daily life.